Effectiveness of haptic feedback devices in preclinical training of dental students-a systematic review - Shankargouda Patil; Shilpa Bhandi; Kamran H. Awan; Frank W. Licari; Marco Di Blasio; Vincenzo Ronsivalle; Marco Cicciù; Giuseppe Minervini (BMC, 2023)
Abstract Background Acquisition of psychomotor skills is of utmost importance for competent preclinical restorative dentistry. Recent advancements in haptic feedback technology have been incorporated into preclinical dental education to augment the conventional phantom head-based training. Objective This systematic review aims to assess the effectiveness of haptic feedback device, Simodont, in improving the skill development and learning outcomes of dental students during their preclinical training. Materials and methods Electronic databases Web of Science, Scopus, PubMed were searched for relevant studies since inception up until March, 2023. Only English language studies that assessed the effectiveness of haptic feedback devices in preclinical dental education were included. We excluded studies that did not use Simodont as the haptic feedback device or did not involve preclinical restorative work. Study quality was assessed using the revised Cochrane risk of bias tool and ROBINS-I. The primary goal of the study is to evaluate the efficacy of Simodont as a complementary training modality for dentistry students. Results Results from 9 high-quality studies were analyzed and synthesized to evaluate the overall impact of haptic feedback devices on various aspects of preclinical training. The studies were conducted on 826 undergraduate dental students enrolled in various years of their training across dental colleges and universities in different parts of the world. A majority of studies showed some concerns regarding risk of bias. Haptic feedback devices added a new layer to Virtual Reality (VR) through the perception of touch and force feedback. It assisted junior dental students improve their psychomotor skills and movement skills. Instantaneous feedback on the students' performance helped enhance their self-assessment and correction, and also eliminated the subjectivity of evaluation. Data derived from virtual simulators helped stratify dental students and predict their clinical performance, providing an opportunity to tailor the learning process to meet individual diversity in students' expertise. Conclusion Based on the limited evidence available, Simodont was effective in preclinical training of dental students, offering advantages such as unlimited reproducibility, objective evaluation of preparation by computer assessment, and cost reduction. And further studies are warranted to explore the incorporation of patient's oral environment simulation for better skill training.